PUBLIC SERVICES BASED ON GOOD GOVERNANCE PRINCIPLES IN THE PACCINONGANG VILLAGE OFFICE, SOMBA OPU DISTRICT, GOWA REGENCY - Putri Novianti; Abdul Halim Talli; Andi Muhammad Akmal (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to explain the implementation of the Principles of Good Governance in Public Services at the Paccinongang Village Office, Somba Opu District, Gowa Regency. This is a qualitative study. The research design is field research. The results of the study indicate that the implementation of the Principles of Good Governance at the Paccinongang Village Office includes: Community Participation, the Supremacy of Law, Transparency, Concern for Stakeholders/the Business World, Consensus Orientation, Equality, Effectiveness and Efficiency, Accountability, and Strategic Vision. There are public service features at the Paccinongang Village Office in Somba Opu District, Gowa Regency, that align with the 9 principles of the Indonesian Transparency Society (MTI) as an actualization of the principles of Good Governance.